The Effectiveness of Public Services in Realizing Good Governance - Ida Bagus Made Putra Dharmika; I Nyoman Subanda (Pandawan, 2023)
Public service is one of the strategic issues in Indonesia because it involves basic needs that must be obtained by society and in its implementation there is interaction between public service providers and the society. Public service can be the benchmark for the success of the performance of the governments, and good governance can be implemented. This research aims to observe and provide solutions in the implementation of public service on Investment and Integrated One Stop Service of (IIOSS) Bali Province to realize good governance. Qualitative descriptive research methods with inductive approaches are used. The data was obtained through interviews, the data was then processed using triangulation methods such as data reduction, data presentation then drawn conclusions. Based on the research results, The quantity and quality of output of IIOSS Bali Province met the 2022 Indonesian Public Service Standards, IIOSS Bali Province Using the online system saves time, simplifies the service process and provides more transparency of information flow to public service recipient, IIOSS Bali Province able to adapt well in response to internal and external changes, by developing a website-based digital service called PRESTISE (Electronically Integrated Licensing), IIOSS Bali Province providing training to the employees the use of technology also Community Satisfaction Survey with service recipients selected as respondents showing score of 93,680 (A-level Quality Service). In conclusion, the effectiveness of Public Services at the Bali Provincial Investment and One-Stop Services Office in realizing good governance has been going well and in line with good governance principles.